Fragmentation issue in Malaysian Industrialised Building System (IBS) projects - Mohd Nawi, Mohd Nasrun; Lee, Angela; Noor, Mohamed; Azman, Azhari; Mohamad Kamar, Kamarul Anuar (School of Engineering, Taylor’s University, 2014)
As a developing country, Malaysian is currently driving for implementing a new or modern construction method, the Industrialis ed Building System (IBS),as an alternative towards enhancing construction performance. Currently, most of the IBS project developments in Malaysia are still conducted by using the traditional construction process approach.This traditional construction process has been widely criticised for its fragmented approach to project delivery and its failure to form effective teams thus created a numb er of issues such as reworks, time delay, rising costs, lack of communication and coordination, and wastages. This paper through literature review aims to highlight this fragmentation issue and clarify how far it affects the process of IBS implementation. Suggestions on how an integrated approach in design and construction in order to minimise the fragmentation gaps will be concluded.